Branched and unbranched ZnO nanorods grown via chemical vapor deposition for photoelectrochemical water-splitting applications. Issue 7 (1st April 2021) - Swathi, S.; Babu, E. Sunil; Yuvakkumar, R.; Ravi, G.; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Velauthapillai, Dhayalan
Abstract: Photoelectrochemical (PEC) water splitting using various semiconductor materials is one of the exciting ways to generate hydrogen and oxygen. Nowadays, electrode fabrication is one of the important tasks and depends on various applications. In the PEC water-splitting application, the synthesized materials can enhance the bandgap by using controlled size and morphology. By altering the bandgap of synthesized nanomaterials, one can enhance the PEC activity and photoconversion efficiency. Recently, ZnO nanostructures have gained much attention due to their attractive and multifunctional properties and have been considered as an outstanding material for fabrication. Therefore, branched and unbranched ZnO nanorods were grown on Indium Tin Oxide (ITO) substrate by chemical vapor deposition (CVD) growth method. The hexagonal phase of the branched ZnO nanorods was confirmed by X-ray powder diffraction pattern. The formation of branched ZnO nanorods was examined by the scanning electron microscopy analysis. Owing to their unique structure, branched nanorods display excellent light absorption capability with good PEC performance. Therefore, branched ZnO nanorods are uniquely excellent material for PEC water-splitting applications.